ANALISIS PENGENDALIAN SOSIAL OLEH GURU TERHADAP SIKAP ANTISOSIAL SISWA-SISWI DI MTSN 1 PONTIANAK - Japri, Japri; Sulistyarini, Sulistyarini; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe title of this study is "Analysis of Social Control By Teacher Against Antisocial Attitudes Students In MTs Negeri 1 Pontianak. The problem in this research is how the social control by the teacher toward the antisocial attitude of the students in MTs Negeri 1 Pontianak (1) preventive (2) repressive and (3) curative. The method used is qualitative with descriptive analysis. The students studied were the students of class VII A. The informants in this study were the Head of School, Teacher Counseling Guidance, Guardians Class VII A, Integrated IPS Teachers andstudent representatives. The data collection tools use observation guides, interview guides and documents. The results of the research (1) Preventive control is before teaching the teacher to give direction to the students how they should behave according to the rules in school and always be honest, during the ceremony the principal always give advice to the students, during the activity of recitation Student Representatives advise students not to forget prayer. (2) Repressive control is done by teachers giving reprimands to students who do not perform the task, the teacher gives punishment to the cheating students, the principal punishes the students who are not orderly during the ceremony and students who are late. (3) Curative control is done by the teacher Teacher Counseling Guidance by calling students and giving awareness to students who are antisocial by providing motivation and guidance.Â Keywords: School Social Control, Antisocial Attitudes, Students of MTsÂ